Insensitivity versus poor response to tumour necrosis factor inhibitors in rheumatoid arthritis: a retrospective cohort study - Ochi, Sae (Arthritis Res Ther, 2020)
BACKGROUND: With advancement in the treatment options of rheumatoid arthritis (RA), optimising the outcomes of difficult-to-treat patients has become increasingly important in clinical practice. In particular, insensitivity to first-line biologic disease-modifying anti-rheumatic drugs (bDMARD) is becoming a significant problem because it may decrease the treatment adherence of patients. This study aimed to compare RA patients with an insensitivity and those with a poor response to initial treatment with tumour necrosis factor inhibitors (TNFis), which are the most frequently used bDMARDs. METHODS: This is a retrospective cohort study using clinical data from the FIRST registry. bDMARD-naïve RA patients treated with tumour necrosis factor inhibitors (TNFis) from August 2003 to May 2019 were included and categorised into three groups: TNFi insensitivity, poor response to TNFis and controls. TNFi insensitivity was defined as follows: (1) discontinuation of TNFi treatment within 22 weeks due to lack of any response, or (2) an increase in the disease activity score in 28 joints–C-reactive protein (DAS28-CRP) of > 0.6 at week 22 compared with week 0. Among the remaining patients, those with a DAS28-CRP > 2.6 at week 22 were categorised in the poor response group. RESULTS: Of the included patients, 94 were classified in the insensitivity, 604 in the poor response and 915 in the control. A higher DAS28-CRP before treatment was a risk factor for a poor response but not for insensitivity. In contrast, dose escalation of infliximab decreased the risk of a poor response but not that of insensitivity. CONCLUSIONS: In future research, poor and insensitivity to bDMARDs should be assessed separately to fully elucidate the aetiology of, and risk factors for, bDMARD refractoriness.